2011
DOI: 10.1002/anie.201104478
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Heteropolyniobates from the Bottom of Group IA

Yu Hou,
May Nyman,
Mark A. Rodriguez

Abstract: Surprising solubility: While it is already well known that [Nb(6)O(19)](8-) salts exhibit an unusual solubility trend, that is, Cs>Rb>K>Na>Li, the heteropolyniobates of Cs and Rb had not yet been crystallized. These very soluble entities have now been obtained from solution by a simple and universal process. New polyoxoniobate geometries are thus unveiled, and the [SiNb(12)O(40)](16-) Keggin ion is characterized in solution for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 40 publications
(50 reference statements)
1
39
0
2
Order By: Relevance
“…Two trimetal clusters are the bow and stern, and two pentametal clusters form the bottom and hull of the boat ( Figure S1 in the Supporting Information). Each niobium atom has a distorted {NbO 6 (6) Å. Furthermore, bond valence sums (BVS) for niobium, germanium, and oxygen atoms were calculated by using the parameters given by Brown, [21] which showed that all the Nb and Ge atoms remain in their highest oxidation states, and could also mean that the Nb species have low activity.…”
Section: Crystal Structures Of 1 Andmentioning
confidence: 99%
See 3 more Smart Citations
“…Two trimetal clusters are the bow and stern, and two pentametal clusters form the bottom and hull of the boat ( Figure S1 in the Supporting Information). Each niobium atom has a distorted {NbO 6 (6) Å. Furthermore, bond valence sums (BVS) for niobium, germanium, and oxygen atoms were calculated by using the parameters given by Brown, [21] which showed that all the Nb and Ge atoms remain in their highest oxidation states, and could also mean that the Nb species have low activity.…”
Section: Crystal Structures Of 1 Andmentioning
confidence: 99%
“…However, PON chemistry studies have focused on isopolyniobate chemistry, which is dominated by the Lindquisttype [Nb 6 O 19 ] 8-anions. [2,3] To date, heteropolyanion chemistry has been dominated by heteropolymolybdates, -tungstates, and -vanadates, which are usually prepared by precipitation from aqueous, acidified solutions at ambient temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…100 Mo or W atoms as individual clusters of three to eight metal centers. 3,4 Until comparatively recently, POMs were restricted to (and numerically dominated by) the elements of groups 5 and 6 usually in their highest oxidation states (d 0 ), but several examples based on d 8 and actinyl metal centers have now been reported, and this new area is currently under active investigation. As the chemistry and structures of the latter bear little relationship with those of the former, it seems appropriate to discuss them separately.…”
Section: Introductionmentioning
confidence: 99%